Slovenian economy in the grip of credit crisis – How to proceed? - Balogh, Imre (Acta Agraria Debreceniensis, 2015)
The Slovenian economy has been through steep ups and downs post-EU accession (2004), and is at the crossroads again. The period 2004–2008 was characterized by balanced monetary and fiscal policies resulting in the adoption of the Euro (2007), coupled with overheated economic growth and propelling corporate indebtedness, fuelled by rapid credit expansion from cheap and abundant foreign funding. The global financial crisis has exposed the “home-grown” vulnerability of the Slovenian economy, bringing about the second largest GDP fall (9.4%) in the Eurozone after Greece, with a double-dip recession (2009, 2012–13). Growth rebounced in 2014 to 2.6% from its low, but the competitiveness of the Slovenian economy continued to slide in international rankings. For further recovery Slovenia, squeezed by high public debt at 82% of GDP, credit contraction despite EUR 5bn state aid injected into the 70% domestically (basically state) owned banking sector, and the continued threat of massive bankruptcy and debt overhang in the corporate sector, has 3 fundamentally different policy options. − Profound restructuring of the banking system and the real sector, on the basis of earnest privatization and voluminous FDI inflow. − Slow creditless recovery due to half-hearted reforms in the financial system and corporate sector. − Substituting wide-ranging micro level restructuring with Government-stimulated credit expansion, reproducing current tensions in even higher magnitudes in the future. In the current state of the Slovenian economy, equity-led growth, combined with far-reaching institutional reforms seems the only choice in laying the foundation for long-term sustainable economic development. This study outlines the critical further steps in re-invigorating the financial system, utilizing also the proposals elaborated by the author and his banking team for the Slovenian macro policy decision-makers.